The Rejection of The Reverse Racism Thesis by the Superior Court of Justice in Brazil: Protection of Historically Discriminated Groups - de Freitas Oliveira, Flaviana; dos Santos Costa, Juliana; Klein, Ana María (Universidad Hemisferios, 2025)
This article critically analyzes the thesis of reverse racism considering structural racism in Brazil, highlighting the importance of its rejection by the Superior Court of Justice (STJ) in a unanimous ruling issued in 2025. The research, of a qualitative nature and based on bibliographic and documentary sources, offers a historical contextualization of racism in Brazil, dismantles the myth of racial democracy, and examines how necropolitics and social labeling affect the lives of Black populations. Within this framework, it discusses the rise of extreme conservatism, which supported by denialist discourses, has popularized the unfounded notion of reverse racism as a tool to delegitimize anti-racist struggles and to reinforce narratives that place historically privileged groups in a position of apparent vulnerability. The STJ ruling, by rejecting the reverse racism thesis, affirms that racism is a structural and historical phenomenon targeting marginalized groups, and that Brazil's anti-racist criminal laws, including the classification of racial injury as a crime, do not apply to situations in which white individuals claim to be victims of discrimination based on skin color. This stance underscores the impossibility of equating deeply unequal conditions and emphasizes that historically privileged groups cannot be treated as minorities. The decision, aligned with international human rights treaties, sets a key precedent by reaffirming that anti-discrimination laws must be interpreted through the historical context of racial exclusion and the constitutional duty to protect marginalized populations.